Awareness and Expectations of E-books: A Study in Tallinn Health Care College. Issue 2 (3rd July 2021) - Kont, Kate-Riin; Piirsalu, Siret
Abstract: Purpose: The current study aims at measuring patron awareness, readiness, usage, and preference regarding electronic books among students and lecturers at Tallinn Health Care College. The results will help the college design future library collections, promote e-books more effectively to reach as many patrons as possible, and encourage patrons to use more e-books. Methodology: An online survey was developed and made available via the institution's Study Information System. The questionnaire was sent to 1, 696 college patrons (including 1, 606 master's degree and higher education students, and 90 academic staff members). Three hundred and forty-six completed questionnaires were returned, and responses were quantitatively and qualitatively analyzed. Results: The survey indicated that most of the respondents are aware of what an e-book is and have used them at least once. Most of the respondents preferred the college to purchase books in both printed and electronic format. The most popular reasons for preferring e-books were not needing to physically borrow the book, having 24/7 access from home, and the ability to download and read e-books on a laptop, smartphone, or tablet. The main reasons for disliking e-books were having to read on a screen, the costs involved, the limitations when printing pages, and the concern that the battery may become discharged during reading. Open access is also highlighted as an alternative to guarantee the availability of scientific information for patrons because the University of Applied Science libraries in Estonia do not get financial support from the government. Originality/Value: Although the college regularly surveys library users' satisfaction with its services, the patrons' attitudes toward e-books has never been studied. The results are valuable to the college. First, the Library Working Group was established by the Estonian Rectors' Conference of Universities of Applied Sciences to change the state funding scheme for acquiring high-quality scientific, scholarly information. Second, there is more emphasis on making open-access e-books more visible on the website, and the addition of new e-books is announced through the college's social-media channels. Third and most important is that the subject Foundation of Research for first-year students will be taught by the college library staff. This gives them the opportunity to encourage and guide students to use e-books.